Overexpression of PtrbHLH, a basic helix-loop-helix transcription factor from Poncirus trifoliata, confers enhanced cold tolerance in pummelo (Citrus grandis) by modulation of H2O2 level via regulating a CAT gene. (1st February 2020) - Geng, Jingjing; Wei, Tonglu; Wang, Yue; Huang, Xiaosan; Liu, Ji-Hong
Abstract: The basic helix-loop-helix (bHLH) family of transcription factors (TFs) plays a crucial role in regulating plant response to abiotic stress by targeting a large spectrum of stress-responsive genes. However, the physiological mechanisms underlying the TF-mediated stress response are still poorly understood for most of the bHLH genes. In this study, transgenic pummelo ( Citrus grandis ) plants overexpressing PtrbHLH, a TF previously identified from Poncirus trifoliata, were generated via Agrobacterium -mediated transformation. In comparison with the wild-type plants, the transgenic lines exhibited significantly lower electrolyte leakage and malondialdehyde content after cold treatment, thereby resulting in a more tolerant phenotype. Meanwhile, the transgenic lines accumulated dramatically lower reactive oxygen species (ROS) levels, consistent with elevated activity and expression levels of antioxidant enzymes (genes), including catalase (CAT), peroxidase and superoxide dismutase. In addition, PtrbHLH was shown to specifically bind to and activate the promoter of PtrCAT gene. Taken together, these results demonstrated that overexpression of PtrbHLH leads to enhanced cold tolerance in transgenic pummelo, which may be due, at least partly, to modulation of ROS levels by regulating the CAT gene.